Reebok rebrands : corporate and marketing strategies in the South African sporting goods industry - Schoombee, Jacques; Bick, Geoff (London : Graduate School of Business, University of Cape Town, 2018)
This case examines the global and local strategies of Reebok to reposition itself as a fitness brand within the sporting industry. The case revolves around PJ Morilee, Reebok South Africa's brand manager, and his efforts to increase Reebok's brand equity which is measured by a monthly NPS score. Having previously worked for Adidas, PJ received the opportunity of re-establishing Reebok in the South African market. PJ believes the strategic and marketing activities should focus on the brand being authentic and credible as this will lead to an increased NPS score, and with it, the brand will grow.The acquisition of Reebok by the Adidas Group in 2006 caused a ripple effect within Reebok. The corporate strategy changed from being a sporting brand competing against the likes of Nike, Puma and Adidas themselves, to being a subsidiary of the Adidas Group focussing on the specialised fitness segment. This affected the brand from a local perspective and it was PJ's responsibility to ensure the local marketing activities represented the global vision of the company.
Originally Published InSchoombee, J., & Bick, G. (2018). Reebok rebrands: Corporate and marketing strategies in the South African sporting goods industry. 2018-13. Cape Town, South Africa: Graduate School of Business, University of Cape Town.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Morilee, P. J; Reebok International Ltd. -- Case studies; Branding (Marketing) -- South Africa -- Case studies; Sporting goods industry -- Marketing -- Case studies; Sporting goods industry -- South Africa -- Case studies